2013
DOI: 10.5732/cjc.011.10344
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter CpG methylation and its translational applications in breast cancer

Abstract: Breast cancer is a complex disease driven by multiple factors including both genetic and epigenetic alterations. Recent studies revealed that abnormal gene expression induced by epigenetic changes, including aberrant promoter methylation and histone modification, plays a critical role in human breast Carcinogenesis. Silencing of tumor suppressor genes (TSGs) by promoter CpG methylation facilitates cells growth and survival advantages and further results in tumor initiation and progression, thus directly contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 105 publications
0
43
0
Order By: Relevance
“…This is especially important because epigenetic changes are emerging as a mechanism involved in toxicantinduced malignant transformation for environmental and occupational carcinogens such as arsenicals, cadmium 1,3-butadine, pesticides, pharmaceutical and biological agents [36][37][38][39]. Epigenetic alterations have been reported in cancer of the breast [40,41], lung [42], prostate [43], cervix [44], colorectal [45,46], esophagus [47], stomach [48], head and neck squamous cell carcinoma [49], urinary bladder [50] and osteosarcoma [51]. This article intends to provide a brief overview of epigenetic changes in GBC.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important because epigenetic changes are emerging as a mechanism involved in toxicantinduced malignant transformation for environmental and occupational carcinogens such as arsenicals, cadmium 1,3-butadine, pesticides, pharmaceutical and biological agents [36][37][38][39]. Epigenetic alterations have been reported in cancer of the breast [40,41], lung [42], prostate [43], cervix [44], colorectal [45,46], esophagus [47], stomach [48], head and neck squamous cell carcinoma [49], urinary bladder [50] and osteosarcoma [51]. This article intends to provide a brief overview of epigenetic changes in GBC.…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2A and PTEN) that are associated with breast cancer development [166]. Generally, these tumor suppressor genes are involved in different carcinogenicrelated processes, such as cell cycle regulation, DNA repair, hormone/receptor-mediated signaling pathways (ER-α), cell apoptosis, and metastasis formation [167].…”
Section: Epigenetic and Breast Cancermentioning
confidence: 99%
“…Few years ago, a genome-wide methylated study demonstrated MCF-7 breast-cancer cell lines that are characterized by both extensive global DNA hypo-methylation and more clustered hyper-methylation at CpG-rich specific loci [237]. In breast cancer, aberrant global methylation is associated with genomic instability and increased activity of oncogenes [238], whereas hyper methylation at promoter CpG sites advance chromatin closing and further silencing of tumor suppressor genes, cell proliferation, and tumor development [167]. Furthermore, promoter hyper-methylation of breast cancer oncogenes tends to inhibit growth regulatory genes, resulting in irregular cell division, whereas global DNA hypo-methylation can stimulate the expression of metastatic genes that are required for cancer cells dissemination [239].…”
Section: Circadian Disruption Biomarkers In Obesity and Cancer Researchmentioning
confidence: 99%
“…Promoter methylation caused by overactive DNA methyltransferases has been implicated in the silencing of ~75 key tumor suppressor genes (TSG) related to breast tumor genesis; these include genes for cell cycle regulation, DNA repair, breast cancer (BRCA1, BRCA2), cell-signaling pathways, and estrogen-α and progesterone receptors [15]. Abnormal histone modification, in combination with DNA hypermethylation, has been associated with epigenetic silencing of TSGs and genomic instability in breast cancer [16]. Histone deacetylase (HDAC) inhibitors are known to induce cell death, as well as impede proliferation of cancer cells, by regulating cell cycle genes by as-yet-unknown mechanisms [17].…”
Section: Introductionmentioning
confidence: 99%